Randomized clinical trial of intraoperative parathyroid gland angiography with indocyanine green fluorescence predicting parathyroid function after thyroid surgery. Issue 4 (6th February 2018) - Vidal Fortuny, J.; Sadowski, S. M.; Belfontali, V.; Guigard, S.; Poncet, A.; Ris, F.; Karenovics, W.; Triponez, F.
Abstract: Background: Hypoparathyroidism, the most common complication after thyroid surgery, leads to hypocalcaemia and significant medical problems. An RCT was undertaken to determine whether intraoperative parathyroid gland angiography with indocyanine green (ICG) could predict postoperative hypoparathyroidism, and obviate the need for systematic blood tests and oral calcium supplementation. Methods: Between September 2014 and February 2016, patients who had at least one well perfused parathyroid gland on ICG angiography were randomized to receive standard follow-up (measurement of calcium and parathyroid hormone (PTH) on postoperative day (POD) 1 and systematic supplementation with calcium and vitamin D; control group) or no supplementation and no blood test on POD 1 (intervention group). In all patients, calcium and PTH levels were measured 10–15 days after thyroidectomy. The primary endpoint was hypocalcaemia on POD 10–15. Results: A total of 196 patients underwent ICG angiography during thyroid surgery, of whom 146 had at least one well perfused parathyroid gland on ICG angiography and were randomized. None of these patients presented with hypoparathyroidism, including those who did not receive calcium supplementation. The intervention group was statistically non-inferior to the control group (exact 95 per cent c.i. of the difference in proportion of patients with hypocalcaemia –0·053 to 0·053; P = 0·012). Eleven of the 50 excluded patients, in whom no well perfused parathyroid gland could be identified by angiography, presented with hypoparathyroidism on POD 1, and six on POD 10–15, which was significantly different from the findings in randomized patients ( P = 0·007). Conclusion: ICG angiography reliably predicts the vascularization of the parathyroid glands and obviates the need for postoperative measurement of calcium and PTH, and supplementation with calcium in patients with at least one well perfused parathyroid gland. Registration number: NCT02249780 (http://www.clinicaltrials.gov ).